Investigating EFL Learners' Views on Applying KAHOOT to Stimulate Learning - Rachman, Dzul; Syarief Fajaruddin (Universitas Sarjanawiyata Tamansiswa, 2024)
Integration of technology into the teaching and learning process is one strategy for increasing the efficiency of the learning process for both students and instructors. Numerous academic work studies have been conducted to evaluate the effects of integrating the Kahoot application into educational settings, with a focus on the academic achievement of students and their subjective evaluations of this technology. Our research objective to fill a vacuum in the literature by examining learners' perspectives of using Kahoot as a learning motivation tool in the English department of a private institution in East Kalimantan. This investigation is of the quantitative research variety. Twenty male and forty-two female participants completed questionnaires as part of this study. This analysis examines the effects, benefits, and challenges associated with the use of Kahoot, as observed through the authors' personal experiences. The participants conveyed their enjoyment and enthusiasm for the activities, perceiving them as a way to improve the classroom environment and make learning more enjoyable. There is a growing interest in determining how the motivation and engagement of learners influence their learning.